Gods huis in de steigers Religieuze gebouwen in ontwikkeling - Verkaaik, Oskar (Amsterdam University Press, 2017)
In this book three anthropologists explore contemporary religious architecture and they develop an original vision on the religious landscape in the Netherlands and Europe. Mosques, synagogues and churches do not only facilitate and symbolize religion, the intimate relationship we have with these buildings touches the essence of what religion is today - in both a positive and a negative sense.